Nanophthalmos: A Review of the Clinical Spectrum and Genetics - Pedro C. Carricondo; Thais Andrade; Lev Prasov; Bernadete M. Ayres; Sayoko E. Moroi (Journal of Ophthalmology)
Nanophthalmos is a clinical spectrum of disorders with a phenotypically small but structurally normal eye. These disorders present significant clinical challenges to ophthalmologists due to a high rate of secondary angle-closure glaucoma, spontaneous choroidal effusions, and perioperative complications with cataract and retinal surgeries. Nanophthalmos may present as a sporadic or familial disorder, with autosomal-dominant or recessive inheritance. To date, five genes (i.e., MFRP, TMEM98, PRSS56, BEST1, and CRB1) and two loci have been implicated in familial forms of nanophthalmos. Here, we review the definition of nanophthalmos, the clinical and pathogenic features of the condition, and the genetics of this disorder.